The Catalogue of Books of 'Abdisho' bar Brikha : Translated with an Introduction and Notes - Stadel, Seth M., (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
This volume presents the first modern annotated translation of ʿAbdishoʿ bar Brikha's (d. 1318) Catalogue of Books , the earliest history of Syriac literature. Along with an English translation, which is based on Yusuf Habbi's 1986 edition, this volume annotates the numerous works listed in the Catalogue by presenting the editions and translations of published works, the manuscripts and sources preserving unpublished works, and the works that do not survive. An extended introduction, an alphabetized listing of the numbered entries and writers, and the vocalized East Syriac text of the Catalogue are also included.